Chapter 15: Thermodynamics - Saifful Kamaluddin, Muzakir; Zainal Abidin, Sulaiman; Siti Hendon, Sheikh Abdullah; Halimah, Mohamed Kamari; Zalita, Zainuddin (SAP Publications Sdn. Bhd., 2011)
Historically, thermodynamics has been explored in order to increase the efficiency of the early steam engines. Thermodynamics is a field of study that deals with energy transformation in a system (normally gas) and thermodynamic processes to change the temperature, volume and pressure of the system.